A De Novo Xp11.23 Duplication in a Girl with a Severe Phenotype: Expanding the Clinical Spectrum - Arican, Pinar; Cavusoglu, Dilek; Gencpinar, Pinar; Ozyilmaz, Berk; Ozdemir, Taha Resid; Dundar, Nihal Olgac (Journal of Pediatric Genetics, 2018)
The Xp11.22–p11.23 duplication syndrome was described in 2009 by Giorda et al and is characterized by intellectual disability, speech delay, and electroencephalography anomalies. We report a case of a 23-month-old girl who presented with epilepsy and global developmental delay and who had a small duplication at Xp11.23. The case we present here is the first case showing the clinical features of Xp11.22–p11.23 duplication syndrome only involving synovial sarcoma, X breakpoint (SSX) genes: SSX1, SSX3, SSX4, and SSX9. This case report contributes to an expanding clinical spectrum of Xp11.22–p11.23 duplication syndrome.
Keywords: duplication syndrome; intellectual disability; microarray analysis